An evaluation of the reliability of the 8-second Skipping with Hand Clapping (8-s SHC) test with the use of the retest method - Podstawski, Robert; Markowski, Piotr; Choszcz, Dariusz; Merino-Marbán, Rafael; Romero-Ramos, Oscar; Curtolo, Cristina (Akademia Wychowania Fizycznego w Poznaniu)
Aim of Study. The aim of this study was to evaluate the reliability of the 8-second Skipping with Hand Clapping (8-sSHC) test performed by young women and men. The presence of a “training trend” was checked during the evaluation. Material and Methods. The study involved 84 female students and 83 male students of the University of Warmia and Mazury in Olsztyn, aged 19-21 years (mean age: 19.44 ± 0.50 and 19.59 ± 0.49, respectively). The reliability of the 8-s SHC test was determined by calculating the values of correlation coefficients between the number of claps in 10 successive repetitions of the test. The “training trend” hypothesis was verified by the Friedman test and post-hoc tests. Results. The values of correlation coefficients between successive repetitions of the 8-s SHC test were within the range of acceptable reliability (0.80-0.90) to good reliability (0.90-0.94) in both genders. Statistically significant differences between the number of claps in successive repetitions of the 8-s SHC test point to the presence of a “training trend”. Those differences were observed up to the fifth repetition in women and men. Conclusions. The 8-s SHC test is a reliable tool for assessing speed abilities among young women and men. The “training trend” should be eliminated before the test is used to evaluate speed abilities. A minimum number of 5 repetitions of the above motor test should be performed in advance for the final test to deliver reliable results. The study has shown that 8-s SHC Test is a reliable tool, which, after developing classification norms, can be used in the process of improving speed abilities for people of different ages.
Keywords: reliability evaluation; retest method; training trend; speed abilities; 8-SHC test; university students